Coordinated emission mitigation mechanism of Beijing-Tianjin-Hebei region in China: a perspective from CO2 emissions embodied in domestic trade. (February 2019) - Fan, Jingli; Meng, Shuo; Wang, Jianda; Zhang, Xian
Abstract: Coordinated emission mitigation is an essential part of regional synergetic development of Beijing-Tianjin-Hebei region. Through compiling an inter-provincial input-output table of China and applying environmentally extended multi-regional input-output model (MRIO), this study seeks to explore the CO2 emissions flow embodied in trade, domestically and internationally, of the Beijing-Tianjin-Hebei region in 2013, where domestic trade and carbon emission sources are both discussed. The findings include: Firstly, the consumption-based emission of Beijing-Tianjin-Hebei region is 818.78 Mt, slightly lower than production-based (963.92 Mt). Secondly, Beijing and Tianjin are net CO2 inflow provinces, with net transferred CO2 emissions 118.85 Mt and 79.22 Mt in 2013 respectively. While Hebei province was an embodied CO2 net outflow region, the emissions transferred out was 162.88 Mt in 2013. Finally, in terms of the composition of the carbon emission sources, the carbon emission in Beijing-Tianjin-Hebei region is closely related from the production-based; but for consumption-based carbon emissions, Beijing and Tianjin is highly dependent on other areas, including Hebei, while the dependence of Hebei on Beijing and Tianjin is quite small.